Development of Learning Media Bowling Letters in Increasing Language Capabilities Early Children - Dewi, Tri Kumala; Mukhtar, Nurkamelia (Devotion : Journal of Research and Community Service, 2022)
This research at developing bowling letters game as learning media in increasing the early childhood language development, and knowing the feasibility of bowling letters as a learning media in developing early childhood language. It was a research and development (R&D) which derives from Borg and Gall. The subject of this research was Play Group of State Kindergarten Perttiwi, Kecepatan Hulu district, Rokan Hulu Regency. Questionnaire validated by material and media experts, principal, and teacher was used for collecting the data. The data obtained was qualitative that was analyzed by the guidelines assessment criteria to determine the quality of bowling letter developed. This research produced a product like bowling letters as learning media based on media expert assessment was 82.6% in very proper category, 85% was from media expert assessment in very proper category, 84.37% was from teacher assessment in very proper category, and 83.75% was the limited trying out in very proper category. And for early childhood language development in the play group, it can be stated as developing because children are able to Pretend to read illustrated stories in books in their own words, Begin to understand two commands given at the same time, Begin to express a desire by saying simple sentences (6 words) and Start telling your experiences with simple stories